IMPLEMENTING DANCE EXTRACURRICULAR ACTIVITIES TO ENHANCE AESTHETIC SENSITIVITY IN EARLY CHILDHOOD EDUCATION - Widiasmara, Lahenda; Rahmadani, Ni kadek aris (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
Aesthetic sensitivity is an important aspect of a child's development, encompassing the ability to appreciate beauty, artistic expression, and to understand and feel aesthetics in art. This study aims to describe how extracurricular dance activities can enhance the aesthetic sensitivity of early childhood students at TK Sekar Nagari UNNES. This research employs a qualitative descriptive approach with data collection techniques including observation, interviews, and documentation. The subjects of the study include all children in TK A and B groups, teachers, and the principal. The data analysis technique used is the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The results of the study show that the implementation of extracurricular dance activities is carried out through the stages of planning, execution, and evaluation, where children actively explore movement, rhythm comprehension, and social interaction during the dance learning process. There is an increase in aesthetic sensitivity reflected in three main aspects: movement, rhythm, and expression. Children are able to coordinate movements harmoniously, respond to rhythm more effectively, and express emotions and imagination expressively through dance. Extracurricular dance activities play an important role in stimulating artistic appreciation in early childhood. The study recommends the development of more varied and interactive dance teaching methods to enhance learning effectiveness and optimally support children's aesthetic development